Shifts in geographical preference for illegal production and distribution of synthetic narcotics in Indonesia - Sulastiana Sulastiana (Cogent Social Sciences)
The escalating crime dynamics at global level related to the illegal production and distribution of synthetic narcotics also occurred in Indonesia with an average annual increase in illegal production of 0.2%, and 58.1% for illegal distribution. The selection of a location for these activities has become a great attraction for the development of this crime. The global assumption is that the selection of location for production and distribution of illegal synthetic narcotics has shifted. This assumption has definitely also become a problem in Indonesia. To conceive this problem, this study takes the theory of crime ecology, location theory, theory of structure and theory of rational choice in clarifying the perpetrator’s perception as is viewed from the social ecology aspect, on the characteristics of location to be selected for the production and distribution of illegal synthetic narcotics, through the process of interaction and rationalization related to location, techniques, as well as the target. Through the mixed method approach, data collection utilizes the technique of structured and unstructured interview to find the perceptual of the perpetrator, and utilizes the confirmatory technique to obtain a deeper understanding of the other variables that may contribute to the selection of location for the production and distribution of illegal synthetic narcotics. Lack of understanding from community and officials requires more exploration to understand determinants’ justification for shifting location characteristics for illicit synthetic production.